Effect of maternal age on the risk of preterm birth: A large cohort study. - Florent Fuchs; Barbara Monet; Thierry Ducruet; Nils Chaillet; Francois Audibert (PLoS ONE, 2018)
Maternal age at pregnancy is increasing worldwide as well as preterm birth. However, the association between prematurity and advanced maternal age remains controversial.To evaluate the impact of maternal age on the occurrence of preterm birth after controlling for multiple known confounders in a large birth cohort.Retrospective cohort study using data from the QUARISMA study, a large Canadian randomized controlled trial, which collected data from 184,000 births in 32 hospitals. Inclusion criteria were maternal age over 20 years. Exclusion criteria were multiple pregnancy, fetal malformation and intra-uterine fetal death. Five maternal age categories were defined and compared for maternal characteristics, gestational and obstetric complications, and risk factors for prematurity. Risk factors for preterm birth <37 weeks, either spontaneous or iatrogenic, were evaluated for different age groups using multivariate logistic regression.165,282 births were included in the study. Chronic hypertension, assisted reproduction techniques, pre-gestational diabetes, invasive procedure in pregnancy, gestational diabetes and placenta praevia were linearly associated with increasing maternal age whereas hypertensive disorders of pregnancy followed a "U" shaped distribution according to maternal age. Crude rates of preterm birth before 37 weeks followed a "U" shaped curve with a nadir at 5.7% for the group of 30-34 years. In multivariate analysis, the adjusted odds ratio (aOR) of prematurity stratified by age group followed a "U" shaped distribution with an aOR of 1.08 (95%CI; 1.01-1.15) for 20-24 years, and 1.20 (95% CI; 1.06-1.36) for 40 years and older. Confounders found to have the greatest impact were placenta praevia, hypertensive complications, and maternal medical history.Even after adjustment for confounders, advanced maternal age (40 years and over) was associated with preterm birth. A maternal age of 30-34 years was associated with the lowest risk of prematurity.